Diferentes substratos na propagação por estaquia de assa-peixe (Vernonia polyanthes Less) - Gomes, J. A.O. [UNESP]; Teixeira, D. A. [UNESP]; Marques, A. P.S. [UNESP]; Bonfim, F. P.G. [UNESP] (FapUNIFESP (SciELO), 2015)
The current study aimed to evaluate the vegetative propagation of assa-peixe using apical cuttings and different substrates. The trial was conducted under greenhouse conditions with controlled irrigation, in the Faculdade de Ciências Agronômicas of UNESP in Botucatu-SP campus. The experimental design was completely randomized, with seven treatments and four replications, with 10 cuttings per replicate. The characteristics were: longest root length, shoot length, number of shoots, rooting percentage, root volume, score of quality of cuttings and dry mass of shoots and roots. The data were subjected to analysis of variance by F test and the averages were compared by the Scott Knott test at 5% probability. For statistical analysis, we used the SISVAR ®. From the analysis, we observed highly relevant effect of the treatments used for all variables, with the exception of the dry weight of shoots, which did not present significant difference. In order to obtain a better rooting of the species concerned, the recommended method would be to use substrates such as clayey soil or medium plus humus in the ratio 1:1.
Different substrates on cutting propagation of assa-peixe (Vernonia polyanthes Less)
Keywords: Cerrado; Humus; Medicinal plant; Vegetative propagation